Error Analysis of Students’ Recount Text Writing – Junior High School Student - Wahyu Indah Mala Rohmana; Puput Jianggimahastu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Students have some difficulties in learning English as foreign language. The problems in four skills often appear especially in writing skill. Writing has some aspects that must be structured according to the system of rules in conducting coherent arrangement of word, clauses, and sentences. Some teachers use guided writing method in developing students’ writing ability which makes student imitate and manipulate the model provided by teacher. The research analyzes semantic error in students’ writing. Most of students in Junior high school have difficulties in producing well-formed sentences. The research is Class Evaluation Research using purposive sampling technique that the sample is taken from 5 students’ text of third grade Junior High School Student in SMPN 1 Maospati. The objective of the study is to examine kinds of error commonly found in students’ text writing. The analysis revealed that Junior High School students’ writing difficulties are commonly in the grammatical prerequisites, lexical semantic property and often interlanguage interference in translation from the first language structure. The numerous errors also include the innapropriate use of the word and grammar in certain context or the form of the sentences. Based on the findings, suggestion for the teachers and students are given. The study concludes that the teacher should teach lexical semantic sense relation, focusing on the correct usage of the verbs and also emphasizing on the grammatical sense